Li isotopes and trace elements as a petrogenetic tracer in zircon: Insights from Archean TTGs and sanukitoids - Bouvier, A.; Ushikubo, T.; Kita, N.; Cavosie, Aaron; Kozdon, R.; Valley, J. (2012)
We report δ7Li, Li abundance ([Li]), and other trace elements measured by ion probe in igneous zircons from TTG (tonalite, trondhjemite, and granodiorite) and sanukitoid plutons from the Superior Province (Canada) in order to characterize Li in zircons from typical Archean continental crust. These data are compared with detrital zircons from the Jack Hills (Western Australia) with U–Pb ages greater than 3.9 Ga for which parent rock type is not known. Most of the TTG and sanukitoid zircon domains preserve typical igneous REE patterns and CL zoning. [Li] ranges from 0.5 to 79 ppm, typical of [Li] in continental zircons. Atomic ratios of (Y + REE)/(Li + P) average 1.0 ± 0.7 (2SD) for zircons with magmatic composition preserved, supporting the hypothesis that Li is interstitial and charge compensates substitution of trivalent cations. This substitution results in a relatively slow rate of Li diffusion. The δ7Li and trace element data constrain the genesis of TTGs and sanukitoids. [Li] in zircons from granitoids is significantly higher than from zircons in primitive magmas in oceanic crust. TTG zircons have δ7Li (3 ± 8‰) and δ18O in the range of primitive mantle-derived magmas. Sanukitoid zircons have average δ7Li (7 ± 8‰) and δ18O higher than those of TTGs supporting genesis by melting of fluid-metasomatized mantle wedge. The Li systematics in sanukitoid and TTG zircons indicate that high [Li] in pre-3.9-Ga Jack Hills detrital zircons is a primary igneous composition and suggests the growth in proto-continental crust in magmas similar to Archean granitoids.